Analisis Dampak Perubahan Arus Amplifier Terhadap Pengoperasian Motor Vibrator Pada Slipform Concrete Paver - Tri Ongko Priyono; Rikko Anugrah Wijaya (JURNAL ELEKTRO, 2024)
Slipform Concrete Paver (concrete printing machine) is one of the equipment in the world of construction and infrastructure, especially in the Rigid Pavement system which aims to cast/print roads in the form of concrete. The use of slipform concrete pavers really supports continuous concrete printing accompanied by guarantees of quality, flatness, slope and very accurate printing points, considering the important role of slipform concrete pavers in casting/printing concrete by checking the amplifier, solenoid valve, generator , and the vibrator motor should get more attention in its maintenance. This study aims to determine the workings of a slipform concrete paver machine that uses a proportional amplifier to the solenoid valve as a proportional valve driver that supplies hydraulic oil to a hydraulic motor to rotate a 3- phase generator that generates electrical energy for a vibrator motor. From the results of the study it was found that the output current from the proportional amplifier greatly affects the output voltage and frequency of the 3-phase generator for the hydraulic motor, then the resistance value of the solenoid valve also determines the hydraulic oil supply that rotates the hydraulic motor as a 3-phase generator player. So the optimal voltage value generated on the 3-phase generator is in the 80 Volt and 110 Volt range, while the optimal frequency value for the 3-phase generator for the vibrator motor is in the 180 Hz and 200 Hz range. the casting material becomes cracked or not good due to trapped air and creates cavities in the casting material